OPTIMALISASI SUMBER DAYA MANUSIA DALAM MENINGKATKAN KUALITAS PELAYANAN PUBLIK: KAJIAN LITERATUR - Apdul Gandi Igirisa; Octaviani Suryaningsih Masaguni; Masran Biahimo; Abdul Madjid Tanta; Rahmat Iksan Djou; Raden Ayu Putri Sasya Sukidjo (Jurnal Multidisipliner Kapalamada, 2026)
This study aims to analyze the role of human resource optimization in improving the quality of public services through a literature review approach. The research employed a qualitative method using a library research approach by examining relevant scientific journals, books, legislation, and policy documents. The findings indicate that human resource optimization can be achieved through competency development, continuous training, strengthening work ethics, profession al development, and the implementation of an integrated performance management system. In addition, transformational leadership, an adap tive organizational culture, and public service motivation significantly contribute to improving service quality. The implementation of the New Public Service principles also encourages public officials to deliver serv ices that are more responsive, accountable & citizen-oriented. The study concludes that human resources are a strategic factor in achieving high-quality public. Sustainable, systematic, & well-planned hu man resource development policies are essential to enhance the capacity of public officials & improve the quality of services provided to the community